The Influence of Investment Knowledge and Minimum Investment Capital on Investment Interest in The Capital Market - Adela Putri, Sofia; Hariyanto, Dedi; Ramdhan Ryanto, Fuad (Journal of World Science, 2023)
This research focuses on the issue of whether investment knowledge and minimum investment capital have a significant influence on investment interest in Pontianak City. The main objective is to analyze the impact of investment knowledge and minimum investment capital variables on investment interest in the capital market in Pontianak City. This study uses a quantitative approach with a population of all investors in Pontianak City, totalling 38,014 investors. The research sample consisted of 100 investors who were selected deliberately (Purposive Sampling). The analysis method in this research uses multiple linear regression analysis, classical assumption testing and hypothesis testing. The results of multiple linear regression analysis show that the regression equation is Y = 31.980 + 0.398X1 – 0.033X2. The correlation coefficient shows an R-value of 0.245, which shows the weak relationship between investment knowledge and minimum investment capital on investment interest. The coefficient of determination shows an R2 value of 0.060, which means that 6.0% of investment interest can be explained by investment knowledge and minimum investment capital. In comparison, other variables not examined in this research influence the remaining 94.0% of investment interest. The results of the simultaneous Test (F test) show that investment knowledge and minimum investment capital simultaneously influence investment interest. The Partial Test (t-test) results on investment knowledge show that investment knowledge has a partially significant effect on investment interest. For minimum investment capital, it can be concluded that minimum investment capital does not have a significant effect on investment interest.